(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents literature data on mastitis, a disease that occurs in dairy animals among farm animals. The article is devoted to a detailed study of clinical signs in goats with mastitis. In addition, methods for diagnosing mastitis and recommendations for treating the disease are given.